Halal Certification and Culinary Traditions: Rethinking Cultural Food Practices in Muslim-Majority Indonesia - Encu M Syamsul; Elis badriah; Nur'aeni Nur'aeni; Anggi Prayitno (Research Synergy Foundation, 2026)
This study explores the relationship between halal certification and culinary traditions in Indonesia, the world's largest Muslim-majority country. Despite the government's efforts to expand halal certification through formal regulations, the extent to which certification influences everyday food consumption practices remains unclear. Using a mixed-methods approach, this research combines quantitative survey data with qualitative interviews involving Muslim consumers and food vendors in Majalengka Regency, West Java. The findings reveal a significant gap between awareness and behavior. While participants generally understand the concept of halal certification and can recognize the official halal logo, most do not consider certification a primary factor in their food purchasing decisions. Instead, food choices are largely influenced by cultural familiarity, affordability, and trust within the local community. Traditional foods are commonly perceived as inherently halal due to their local origins and preparation by Muslim vendors. The study concludes that halal certification functions more as a regulatory mechanism than as a cultural determinant of consumption behavior. These findings highlight the importance of developing culturally grounded halal governance that bridges formal regulatory frameworks and community-based values. This research contributes to the broader discourse on religion, culture, and governance by demonstrating that halal practices in Indonesia are shaped not only by institutional compliance but also by social trust, cultural traditions, and everyday ethical considerations.